2016
DOI: 10.1007/s00405-016-3946-0
|View full text |Cite
|
Sign up to set email alerts
|

Coblation nasal septal swell body reduction for treatment of nasal obstruction: a preliminary report

Abstract: In this paper, we present the results of coblation nasal septal swell body (NSB) reduction for the treatment of nasal obstruction in patients with abnormally thickened NSB. The study design was a retrospective clinical series conducted at a single tertiary medical center. Eight patients underwent coblation NSB reduction. Pre-operative and post-operative nasal functions were evaluated by acoustic rhinometry and subjective symptom scales. We also analyzed pre-operative CT scan images and nasal endoscopic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Arslan et al [16] stated an NSB width ≤8 mm as 'normal'. In a study of Kim et al, [9] the mean width for the markedly enlarged NSB was 16.4±2.2 mm. From this standpoint, we defined NSB's larger than 1.5 cm as 'markedly enlarged' NSB.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Arslan et al [16] stated an NSB width ≤8 mm as 'normal'. In a study of Kim et al, [9] the mean width for the markedly enlarged NSB was 16.4±2.2 mm. From this standpoint, we defined NSB's larger than 1.5 cm as 'markedly enlarged' NSB.…”
Section: Discussionmentioning
confidence: 85%
“…Since the central part of the NSB nearly corresponds to the nasal valve region, enlargement in this structure can cause airway resistance. [9][10][11][12] Kim et al, [9] showed that by decreasing NSB volume, the nasal valve area can be expanded. If the relatively narrow distal nasal valve section is considered, even very small changes in NSB dimensions may have significant consequences on nasal resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Swell body reduction has been successfully performed for nasal obstruction. 17,18 The potential effect of septal perforation on the NSB has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal obstruction has various methods of treatment, related to the etiology. For example, in case of nasal turbinate hypertrophy or septal deviation, surgical approach is considered the mainstay treatment 1,13 .…”
Section: Treatment Of the Nasal Swell Bodymentioning
confidence: 99%